Workshop on implementation strategies for piloting flood index insurance for agricultural development in Bangladesh - International Water Management Institute (International Water Management Institute, 2017)
International Water Management Institute (IWMI) with the support from CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and Water, Land and Ecosystems (WLE) and Ministry of Agriculture, Forestry and Fisheries (MAFF, Japan), agreed to develop innovative financial risk transfer solutions particularly suitable for implementing in countries with large small holding farming communities against flood losses. IWMI along with the its partners has now developed an innovative Index-based flood insurance1 (IBFI) scheme to be piloted in two countries Bangladesh and India to increase the short term coping capacity of small holding farmers against flood risk. Sirajganj in Bangladesh and Muzzafarpur district in India are selected for IBFI pilot. The current stage of IBFI2 project requires additional efforts focusing on piloting the project in Bangladesh and India during the 2017 monsoon season. This innovative approach aims streamline and fasten effective insurance payouts, so that it money reaches affected farmers in timely manner. The project integrated advanced numerical modelling techniques for constructing long term flood patterns, high resolution remote sensing data and statistical models to predetermine flood thresholds, which could trigger speedy compensation payouts. Effective end-to-end solutions is being developed in collaboration with a range of organizations and experts from central and state government bodies, private insurance firms, community-based organizations (CBOs) and nongovernmental organizations (NGOs). The workshop is jointly organized by IWMI and IWM.